Analysis of Rotor-Side Control and Grid-Side Controls for Grid Voltage Improvement in a DFIG-Based Wind Turbine System - Alsabah, Mus Ali; Rini Nur Hasanah; Wijono; Corina Martineac (Faculty of Engineering, Universitas Brawijaya, 2023)
Wind Power Plant (PLTB) has received a lot of attention from the public, researchers, and the government because of its advantages and role in reducing the causes of environmental damage due to the generation of electrical energy. Unlike power plants that use primary energy from fossil fuels, PLTB uses wind kinetic energy to generate electricity. Many problems arise because the wind speed is always changing every time. The resulting output voltage instability in the generator can affect the electric power system where the output electricity of the generator is injected. This paper describes how to analyze the generator output voltage control at PLTB. The generator used is a type of induction generator with two inputs (Double-Fed Induction Generator, DFIG). while the method of analysis is carried out using the PSIM simulation tool from Powersim, Inc. Control is carried out both on the rotor side (Rotor Side Converter, RSC) and on the grid side (Grid Side Converter), with the aim of maintaining the output voltage injected into the power grid with a certain level of voltage oscillation. The control results show that the generator output voltage can be maintained as desired.